A La-doped ZnO ultra-flexible flutter-piezoelectric nanogenerator for energy harvesting and sensing applications: a novel renewable source of energy. Issue 29 (16th July 2019) - Pandey, Rajagopalan; Khandelwal, Gaurav; Palani, Iyamperumal Anand; Singh, Vipul; Kim, Sang-Jae
Abstract : Doped zinc oxide nanorods synthesized via a wet chemical approach were used to fabricate an ultra-flexible flutter-piezoelectric nanogenerator (UF-PENG) for superior energy harvesting and self-powered sensing applications. Abstract : Zinc oxide nanorods synthesized via a wet chemical approach were used to fabricate an ultra-flexible flutter-piezoelectric nanogenerator (UF-PENG). The UF-PENG has demonstrated good capabilities to act as not only an energy generator but also a wind velocity/direction sensor. Using the same procedure, the ZnO nanorods have been doped with lanthanum, and the doped device was found to exhibit three times the output of intrinsic PENG. Furthermore, through the process of annealing, the output of the PENG was enhanced. Peak power density calculations, capacitance charging, and stability analysis (1500 cycles) were performed. We have implemented this approach to make an ultralightweight/sensitive and wind modulated device which can flutter in low wind speed and can operate under a light breeze (2.8–3.8 m s −1 ). The device was able to harvest a voltage of over 1.6 V at 3.8 m s −1 . The observed results indicate that the developed device could work as a self-powered wind velocity sensor. It can also function as a wind direction sensor (0–90°). Finite element simulation was performed to investigate the underlying mechanism. Additionally, the stability analysis of the sensor for more than 4500 cycles was conducted, and the obtained results showed the high stability of the device.